Uncovering es teh indonesia’s business model: BMC study and recommendations for growth - Widiyanti, Wiwik; Susilowati, Isnurrini Hidayat; Rani, Rani; Syahrir, Syahrir (Institute of Computer Science (IOCS), 2024)
Ice Tea Indonesia belongs to the category of well-known beverages consumers. Like business in general, The Indonesia is facing many challenges. The aim of this study is to give recommendations for the correct strategy of BMC and SWOT analysis. In terms of strength, Ice Tea Indonesia has a varied product, affordable prices, extensive outlet network, and a strong brand image. However, weaknesses include dependence on foreign tea raw materials and a lack of product innovation. Opportunities are high market demand and potential expansion abroad. Threats involve tight competition and changing customer tastes. Strategic recommendations include leveraging internal powers to harness external opportunities,ining market share, and anticipating threats through risk and crisis management